Hybrid Solar and Coal-fired Steam Power Plant with Air Preheating Using a Centrifugal Solid Particle Receiver. (May 2015) - Prosin, T.; Pryor, T.; Creagh, C.; Amsbeck, L.; Buck, R.
Abstract: Coal power stations have been hybridised with concentrated solar thermal (CST) fields which producefeedwater or with turbine bleed steam (TBS) heating from directlinear Fresnel to steam technology. This paper assesses solar hybridisation of boiler based steam power plants, whichpreheat boiler combustion air with a novel high temperature CST system based on a solid particle receiver (SPR). This new method of preheating has the potential to increase the solar share of the overall system, improve fuel saving and therefore produce a higher solar to electric conversion efficiency. These benefits result from theSPR solar systems higher operating temperature and integrated thermal storage. The integrated thermal storage also allows a buffered response time for handling transients in the intermittent solar resource. Analysis indicates that air-solarisation of coal plants can result in significantly higher solar to electric conversion efficiency than existing solar hybridisation options. Solarisation by TBS decreases power cycle efficiency due to bleed steam reduction, while solarisation by air-preheating increases the power system efficiency, primarily due to enhanced boiler efficiency brought about by reduced stack losses. The air solarisation option proposed in this paper has beencompared to current TBS with Fresnel based technology. The comparison was conducted by modelling both systems and analysing the thermodynamic heat and mass balance of the steam cycle and boiler using EBSILON®Professional software. Annual simulation tools, which calculate the performance of the solar field, receiver, storage (when applicable) and other system components, were used to model the output of the solar technologies. These tools, coupled with available economic data and cost models for the newly developed solar components, were used to calculate the levelized cost of energy of the compared hybridisation options. It was calculated that the levelized cost of the solar electricity produced by the SPR system was approximately 59%theelectricity produced by the Fresnel hybridisation.